Pengelolaan Sumber Daya Alam dan Akibat Hukum Bagi Lingkungan Hidup Perspektif Hukum Lingkungan Internasional - Adjeng C M Tethool; Josina Augustina Yvonne Wattimena; Marthinus Kainama (Faculty of Law, Universitas Pattimura, 2022)
Introduction: Management of natural resources that is not in accordance with international problems such as air pollution. Pollution that occurs in the air environment due to forest fires that occurred in Indonesia, especially in 2019 in Riau Province, is not in line with the principles of international environmental law.Purposes of the Research: The purpose of this research is to analyze and find out about the prevention of air pollution and the legal consequences of managing natural resources that pollute the air environment based on international environmental law. Methods of the Research: The research method in this study is a normative legal research, using a law approach and a conceptual approach. Sources of research data include primary, secondary, tertiary legal sources. Data collection techniques in the form of literature study. Processing and analysis of legal materials used in writing is using qualitative analysis method.Results of the Research: I The results of this study that the management of natural resources is carried out not in accordance with the principles of international law, causing air pollution which has a negative impact on the State of Indonesia and also for the State of Malaysia, Singapore. From this research, it is also not allowed to take preventive action through supervision carried out through the government of the State of Indonesia.